Comparative Study of Fuzzy Logic Mobility Based FLM-AODV Routing Protocol and AODV in MANETs - Vivek Sharma; Bashir Alam; M. N. Doja (Institute of Advanced Engineering and Science, 2017)
In mobile ad hoc wireless networks (MANETs), traditional protocol like AODV performs well for low mobility of nodes but not for high node mobility. So, it becomes important to consider mobility factor during the path selection procedure of routing protocol. Here, a fuzzy logic mobility based protocol (FLM-AODV) that considers the mobility factor is proposed. Due to the consideration of mobility factor, the proposed protocol has better performance than the traditional AODV. The experiment results show that the proposed protocol has advantages of improved average end-to-end delay and packet delivery ratio (PDR) over existing AODV protocol.